Acta et Decreta (Uniao Grafica, 1929)
Stamp of St. Joseph Seminary
Keywords: 1.Conservation 保護; 2.Damage

Actas do Conselho do Governo (Imprnsa Nacional de Macau, 1929)
Keywords: 1.Conservation 保護; 10.Cover Damage; 2.Damage; 6.Yellowing 變黃

Actas do Conselho do Governo (Imprnsa Nacional de Macau, 1929)
Keywords: 1.Conservation 保護; 10.Cover Damage; 2.Damage; 6.Yellowing 變黃

Boletim Oficial da Colonia de Macau (Imprensa Nacional, 1929)
Keywords: 1.Conservation 保護; 18.Bookworm

Le Jubile' Sacerdotal de S. S. Pie Xi (1929)
Stamp
Keywords: 1.Conservation 保護; good

Logica et Introductio in Philosophiam Christianam (Typis et Sumptibus Feliciani Rauch, 1929)
Stamp of St. Joseph Seminary
Keywords: 1.Conservation 保護; Good

Manual of Christian Doctrine (John Joseph McVey, 1929)
Keywords: 1.Conservation 保護; 6.Yellowing 變黃; Fair

Model English Chinese Dictionary (1929)

Obstacles A L'apostolat (Editions du Museum Lessianum, 1929)
Stamp of St. Joseph Seminary
Keywords: 1.Conservation 保護; 2.Damage; 6.Yellowing 變黃

Manual do Apostolado da Oracao - Abranches, Santos (Livraria do Apostolado da Imprensa, 1929)
Keywords: 1.Conservation 保護; 10.Cover Damage; 18.Bookworm; 2.Damage

Curso de Liturgia Romana (Revista Opus Dei, 1929)
stamp of seminario de s. jose, sign
Keywords: 18.Bookworm; Fair

Un Grand Educateur, Le Bienheureux Don Bosco - Auffray, A. (Librairie Catholique Emmanuel Vitte, 1929)
Keywords: 1.Conservation 保護; 10.Cover Damage; 2.Damage; 6.Yellowing 變黃

De ecclesiae sacramentis: commentarius in tertiam partem S. Thomae - Billot, Louis (Universitatis Gregorianae, 1929)
Keywords: 18.Bookworm; Condition: Fair; Sacraments; Sacrements; Summa theologica (Thomas, Aquinas, Saint); Thomas, Aquinas, Saint, 1225?-1274; Travel

Science and religion: lectures delivered in St. Patrick's Hall, January and February, 1929 (no. 4 in October 1927) - Byrne, G.; Gallagher, R. W.; Joy, P. (The Rock Office, 1929)
Keywords: Apologetic writings; Apologetics; Catholic Church; Catholic Church Apologetic works; Église catholique Ouvrages apologétiques

La Devocion al Corazon de Jesus - Caniz, Florentino Al (Pedidos: Las Marias, S. Jeronimo, 1929)
Keywords: 1.Conservation 保護; 6.Yellowing 變黃; Fair

Selecta Ex Optimis Latinitatis Auctoribus vol. Terium - Cicero, M. T. (Eugenius Subirana, 1929)
Keywords: Literatura latina antologías

Biblioteca do Lar Cristao - Climaco, Joao (O ultimo e o mais indigno Presbitero da Diocese de Macau, 1929)
Keywords: 1.Conservation 保護; 10.Cover Damage; 15.Stain 污漬; 2.Damage

Logica et Introductio in Philosophiam Christianam - Donat, Josephus (Typis et Sumptibus Feliciani Rauch, 1929)
Stamp of St. Joseph Seminary
Keywords: 1.Conservation 保護; 2.Damage

Notiones Scripturae Sacrae, Introductio Generalis - Duvigneau, E. (Typis Pe-t'ang, 1929)
Keywords: Good

Elementa Philosophiae, Aristotlico-Thomisticae - Gredt, Ios. (Herder & Co., Typographi Editores Pontificii, 1929)
Stamp of St. Joseph Seminary
Keywords: 1.Conservation 保護; 18.Bookworm; 2.Damage; 6.Yellowing 變黃

Hermeneutica Sacra Seu Introductio In Omnes Libros Sacros Veteris Ac Novi Foederis - Ianssens, I. H. (Ex Officina Libraria Martietti anno 1820 condita, 1929)
Stamp of St. Joseph Seminary
Keywords: 1.Conservation 保護; 10.Cover Damage; 2.Damage; 6.Yellowing 變黃

Novo Regimento do Cabido - Joseph Ep (Orfanato Imaculada Conceicao, 1929)
Stemp of St. Joseph Seminary
Keywords: Good

When Mary Walked the Earth - Lord, Daniel A. (The Queen's Work, 1929)
Keywords: 1.Conservation 保護; 18.Bookworm; 2.Damage

Les Missions De Chine et Du Japon - Planchet, J. M. (Imprimerie des Lazaristes, 1929)
Stamp of St. Joseph Seminary
Keywords: 1.Conservation 保護; 18.Bookworm; 6.Yellowing 變黃; Fair

De Principiis Theologiae Moralis - Schmitt, A. (Typis et Sumptibus Feliciani Rauch, 1929)
Stamp of St. Joseph Seminary
Keywords: 1.Conservation 保護; 10.Cover Damage; 2.Damage

Carmina Latina - Seraphim, Joao (Typis Privatis Santissimi Cordis Jesu, 1929)

A Caminho da Terra Santa - Tercas, J. Alves (Edicao e Propriedade do Autor, 1929)
Keywords: 1.Conservation 保護; 15.Stain 污漬; Fair

溫特渥斯平面幾何學 - Wentworth, G. A. (商務印書館, 1929)
Keywords: 平面几何

新撰初級中學教科書 世界史 (上冊) - 周, 傳儒 (商務印書館, 1929)

學生指南 - 歐, 元懷 (勤奮書局, 1929)

西洋製譜學提要 - 王, 光祈 (音樂叢刊, 1929)
Keywords: Composition (Music); Composition (Musique)

新撰初級中學教科書 本國地理 (下卷) - 繆, 育南 (商務印書館, 1929)

中國文學史綱 - 蔣, 鑑璋 (亞細亞書局, 1929)

辭源 上冊 - 陸, 爾奎 (商務印書館, 1929)
Keywords: Chinese language; Chinese language Dictionaries; Chinois (Langue) Dictionnaires; Dictionaries; Dictionary; Dictionnaires; dictionaries

辭源 下冊 - 陸, 爾奎 (商務印書館, 1929)
Keywords: Chinese language; Chinese language Dictionaries; Chinois (Langue) Dictionnaires; Dictionaries; Dictionary; Dictionnaires; dictionaries